1992
DOI: 10.1357/002224092784797700
|View full text |Cite
|
Sign up to set email alerts
|

Water characteristics, mixing and circulation in the Bay of Bengal during southwest monsoon

Abstract: Influence of the freshwater influx, the wind forcing and the Indian Ocean monsoon drift current on the property distributions and the circulation in the Bay of Bengal during southwest monsoon has been quantified. At the head of the Bay, waters of low salinity, affected by the freshwater influx, occupy the upper 90 m water column. The isohaline 34.0 x 10-3 separating these waters from those of underlying saline waters shoals southward gradually and outcrops around 14N, ION and 6N in the western, central and sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(94 citation statements)
references
References 3 publications
8
86
0
Order By: Relevance
“…If the salinity of the outflow is 33 psu, 34 psu, or 34.5 psu, the averaged required outgoing volume transport is 1.65 Sv, 3.5 Sv, or 6.9 Sv, respectively. Observations show that high-salinity water from the Arabian Sea enters the BoB between 80°E and 90°E during the southwest monsoon season (June to September; e.g., Murty et al, 1992;Vinayachandran et al, 2013;Figure 7a,b in Gordon et al, 2016, in this issue), and this has been replicated in several models (e.g., Vinayachandran et al, 1999;Han and McCreary, 2001;Jensen, 2001). More recently, observations and…”
Section: Exchanges Between the Equatorial Region And The Bay Of Bengalmentioning
confidence: 75%
“…If the salinity of the outflow is 33 psu, 34 psu, or 34.5 psu, the averaged required outgoing volume transport is 1.65 Sv, 3.5 Sv, or 6.9 Sv, respectively. Observations show that high-salinity water from the Arabian Sea enters the BoB between 80°E and 90°E during the southwest monsoon season (June to September; e.g., Murty et al, 1992;Vinayachandran et al, 2013;Figure 7a,b in Gordon et al, 2016, in this issue), and this has been replicated in several models (e.g., Vinayachandran et al, 1999;Han and McCreary, 2001;Jensen, 2001). More recently, observations and…”
Section: Exchanges Between the Equatorial Region And The Bay Of Bengalmentioning
confidence: 75%
“…The Bay of Bengal sector of the Indian Ocean has been poorly sampled until recently. Murty et al (1992) provide unique results based on a coarse array of temperature and salinity observations within the Bay of Bengal during the southwest monsoon. Bhat et al (2001) report on the recent BOBMEX observations during July and August 1999.…”
Section: Initial Results From the Fieldmentioning
confidence: 99%
“…This results in a very large lateral haline gradient. From a time series of hydrographic observations conducted in the northern BoB during the summer of 1984 on board ORV Sagar Kanya, Murty et al (1992) reported the large SSS gradient from the open bay (35 psu) toward the northern BoB (16 psu). The WOA05 well captures this spatial distribution with, for example, low salinity from the river runoff (e.g., 20.5 psu in December at 218N, 888E) that increases sharply toward the center of the bay (32.8 psu at 158N, 888E in December).…”
Section: Design Of Experiments and Validation Of Salinity Fieldsmentioning
confidence: 99%